Communicational and cultural competence in translation of the students of 6th semester in ECCI (2017)
The translation is a field that has been studied and considered for a lot of scholars and linguists, wanting to stand out not only the importance of translating successfully a message to another dialect or language, but also showing the methods, techniques and effective ways of creating a translation from its beginning to its end, which is the moment when the recipient obtains the translated message. One of the competences that are important in the translation context, are the communicational and cultural competence, because in the translation, the meaning of the culture is too difficult to understand, therefore, the communicational and cultural competence must take part in this process to guarantee the effectiveness of the translation. The word “culture” has different meanings depending on the context in which is used. For that reason, is significant to define culture, according to Schwartz, S. H. (1992) ‘Culture consists of the derivatives of experience, more or less organized, learned or created by the individuals of a population, including those images or encodements and their interpretations (meanings) transmitted from past generations, from contemporaries, or formed by individuals themselves.’ Another definition of culture is “Language, as a part of the cultural core, is at the heart of culture. What people do with language – narrative, poetry, songs, plays, etc – are soft expressions of a culture; they are faces of culture